Career discovery encyclopedia - Summerfield, Carol J., 1960-; Ashby, Susan (Chicago : Ferguson Pub. Co., 1993)
Six volumes with 504 articles on all categories of occupations with such information as description of the job, earnings, educational and training requirements, addresses to get more information, and other pertinent facts.
v. 1. A - City managers -- v. 2. City planners - Fas -- v. 3. FBI - Librarians -- v. 4. Library - Par -- v. 5. Pat - Scr -- v. 6. Scu - Zoo.
Includes indexes.
Keywords: Vocational guidance -- Dictionaries -- Juvenile literature; Vocational guidance -- Dictionaries; Occupations